Conductive carbon paste capable of being used for perovskite solar cell and preparation method and application of conductive carbon paste
By adding self-assembled small molecule additives to the conductive carbon slurry of perovskite solar cells, the work function of the carbon electrode is regulated, and the energy level mismatch between the perovskite layer and the carbon electrode is solved, which significantly improves the photoelectric conversion efficiency and stability of the solar cell.
Patent Information
- Application Number
- CN202411527841.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-30
- Publication Date
- 2025-04-04
AI Technical Summary
Based on the large energy level mismatch between the perovskite layer and the carbon electrode in perovskite solar cells, the hole transfer rate is slow, the interface charge accumulation and recombination loss is limited, the photoelectric conversion efficiency of carbon-based perovskite solar cells is limited.
By adding self-assembled small molecule additives to the conductive carbon slurry, the work function of the carbon electrode is regulated, the energy level matching degree and interface contact between perovskites and carbon electrodes are improved, the hole extraction efficiency is improved, and carrier recombination is suppressed.
It significantly improves the photoelectric conversion efficiency of carbon electrode perovskite solar cells, improves the stability and performance of the device, and reduces the preparation cost.
Smart Images

Figure CN119763898A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the field of solar cells, and in particular relates to a conductive carbon paste that can be used for perovskite solar cells, and a preparation method and application thereof. Background Art
[0002] At present, the photoelectric conversion efficiency of solar cells based on perovskite materials has exceeded 26%, which is comparable to commercial crystalline silicon solar cells and is expected to become the next generation of solar cells. However, this type of high-efficiency perovskite solar cell device structure often uses precious metal electrodes and hole transport materials, which has potential factors that are not conducive to further commercial applications. First, the metal electrode is easily corroded by reacting with the components of the perovskite light absorption layer, which reduces the stability of the device; second, the metal and hole transport materials used, as well as the preparation equipment and process are expensive, which increases the cost of device preparation. Carbon materials are ideal for replacing metal electrodes because they have the advantages of low price, good conductivity, excellent chemical stability and suitable work function. At the same time, carbon electrodes have a certain hole extraction ability and can prepare devices without hole transport layers. Therefore, perovskite solar cells based on carbon electrodes can improve the stability of the device while reducing the preparation cost. Conductive carbon slurry is the raw material for preparing carbon electrodes.
[0003] However, compared with traditional metal electrode devices, the photoelectric conversion efficiency of carbon electrode devices is still far behind. The key factor limiting the efficiency improvement of carbon-based perovskite solar cells without hole transport layers is mainly the large energy level mismatch between the perovskite layer and the carbon electrode, which slows down the transmission rate of holes from the perovskite to the carbon electrode, causing interfacial charge accumulation and recombination losses. It can be seen that the electrical properties of the carbon electrode itself have a great influence on the performance of the device. Therefore, in order to obtain high-efficiency carbon-based perovskite solar cells, it is necessary to effectively control the work function of the carbon electrode, that is, to design and optimize the composition of the conductive carbon paste. Summary of the invention
[0004] In order to overcome the shortcomings and deficiencies of the above-mentioned prior art, the primary purpose of the present invention is to provide a carbon electrode slurry that can be used for perovskite solar cells. It regulates the work function of the carbon electrode through self-assembly small molecule additives, improves the energy level matching between the carbon electrode and the perovskite, and improves the interface contact between the carbon electrode and the perovskite film, which can significantly improve the performance of carbon electrode perovskite solar cells and has good application potential.
[0005] Another object of the present invention is to provide a method for preparing the above-mentioned carbon electrode slurry that can be used for perovskite solar cells.
[0006] The present invention aims to provide the use of the above-mentioned carbon electrode slurry that can be used for perovskite solar cells in perovskite solar cells.
[0007] The purpose of the present invention is achieved through the following solutions: A conductive carbon paste that can be used for perovskite solar cells comprises a conductive carbon material, a solvent, a binder, and an additive.
[0008] Optionally, the conductive carbon material is a carbon material with good conductivity, including but not limited to at least one of carbon black, graphite, graphene, carbon nanotubes, etc.
[0009] Optionally, the solvent used is at least one of isopropyl titanate, tetrabutyl titanate, butyl acetate, ethanol, terpineol, ethyl acetate, glacial acetic acid, γ-butyrolactone, etc., but is not limited thereto.
[0010] Optionally, the binder is at least one of ionic liquid, ethyl cellulose, polyvinyl acetate (PVAc), hydroxypropyl cellulose, polyvinyl pyrrolidone (PVP), polymethyl methacrylate (PMMA), etc., but is not limited thereto; wherein the ionic liquid includes but is not limited to at least one of 1-octyl-3-methylimidazolium hexafluorophosphate, 1-butyl-3-methylimidazolium hexafluorophosphate, etc.
[0011] Preferably, the additive is an organic small molecule having a donor-acceptor-anchor group that can form a self-assembled molecular layer, and the structural composition of the molecule includes an anchor group, a spacer group and a functional group. The functional group includes but is not limited to at least one of carbazole, triphenylamine, thiophene, phenothiazine, triazaanthracene, graphene, etc. The spacer group includes but is not limited to at least one of an aliphatic chain and an aromatic ring. The anchor group includes but is not limited to at least one of phosphonic acid, carboxylic acid, cyanoacetic acid, cyanophosphoric acid, sulfonic acid, silane, etc.
[0012] Preferably, the additive is at least one of [2-(9H-carbazol-9-yl)ethyl]phosphonic acid (abbreviated as 2PACz) and [2-(3,6-dimethoxy-9H-carbazol-9-yl)ethyl]phosphonic acid (abbreviated as MeO-2PACz).
[0013] In the conductive carbon paste that can be used for perovskite solar cells, the amounts of conductive carbon material, solvent, binder, and additives meet the following requirements: the mass of the conductive carbon material accounts for 25-40% of the mass of the conductive carbon paste, the mass of the solvent accounts for 50-65% of the mass of the conductive carbon paste; the mass of the binder accounts for 6-12% of the mass of the conductive carbon paste; and the mass of the additive accounts for 0.1-2.0% of the mass of the conductive carbon paste.
[0014] The present invention also provides a method for preparing the conductive carbon slurry that can be used for perovskite solar cells, which comprises the following steps: after mixing the raw materials together, grinding or stirring so that the obtained slurry is in a state of being evenly mixed, free of obvious visible particles, and having fluidity, so as to obtain the conductive carbon slurry that can be used for perovskite solar cells.
[0015] The grinding can be performed by planetary ball mill or manual grinding.
[0016] The present invention also provides the use of the above-mentioned conductive carbon paste for perovskite solar cells in perovskite solar cells, especially in the preparation of carbon counter electrodes for perovskite solar cells.
[0017] A carbon counter electrode for a perovskite solar cell is prepared by using the above-mentioned conductive carbon slurry that can be used for perovskite solar cells by means of scraping, screen printing, etc.
[0018] The present invention also provides a perovskite solar cell, which comprises a carbon counter electrode prepared by the above-mentioned conductive carbon slurry that can be used for perovskite solar cells, a perovskite layer and an electron transport layer.
[0019] The perovskite solar cell has an ABX3 structure, wherein A is at least one of methylamine, formamidine, cesium and rubidium, B is at least one of lead, tin, silver, antimony, copper and bismuth, and X is at least one of chlorine, bromine, iodine, thiocyanate and acetate. Methods for preparing perovskite films include but are not limited to spin coating, vapor deposition, slit coating, blade coating or spray coating.
[0020] In the perovskite solar cell, the electron transport layer includes but is not limited to SnO 2 , TiO 2 , at least one of ZnO, PCBM, C60, etc.
[0021] Optionally, the perovskite solar cell may also have a hole transport layer, including but not limited to a hole transport layer made of at least one of small molecules, polymers, and inorganic hole transport materials. A structure without a hole transport layer may also be used.
[0022] Compared with the prior art, the present invention has the following advantages and beneficial effects: The self-assembling small molecule additives added to the slurry can effectively regulate the work function of the carbon electrode, reduce the energy level difference between the perovskite and the carbon electrode, enhance the built-in electric field at the interface between the perovskite and the carbon electrode, accelerate the hole extraction process, inhibit carrier recombination, and improve the photoelectric conversion efficiency of the device.
[0023] The conductive carbon paste provided by the present invention can be formed into a film by methods such as scraping, screen printing, roll-to-roll printing, etc. under low temperature conditions, has low energy consumption, fast drying, good conductivity, and is suitable for large-area preparation. BRIEF DESCRIPTION OF THE DRAWINGS
[0024] Figure 1 It is a current-voltage (JV) curve of the perovskite solar cell prepared by the conductive carbon paste of Examples 1-2 of the present invention and Comparative Example 1.
[0025] Figure 2 SEM photos of the carbon counter electrodes prepared in Examples 1-2 and Comparative Example 1, wherein (a), (c), and (e) are front plan views of the carbon counter electrodes of Comparative Example 1, Example 1, and Example 2, respectively, and (b), (d), and (f) are cross-sectional views of the carbon counter electrodes of Comparative Example 1, Example 1, and Example 2, respectively. DETAILED DESCRIPTION
[0026] The present invention is further described in detail below in conjunction with the examples and drawings, but the embodiments of the present invention are not limited thereto. If specific conditions are not specified in the examples, they are carried out according to conventional conditions or conditions recommended by the manufacturer. If the manufacturer of the reagents or instruments used is not specified, they are all conventional products that can be purchased commercially.
[0027] The invention provides a conductive carbon slurry for a perovskite solar cell, which comprises an organic solvent, a binder, an additive and a conductive carbon material. The organic solvent is butyl acetate, the binder is polymethyl methacrylate (PMMA), the conductive carbon material is graphite and conductive carbon black, and the additive comprises [2-(9H-carbazole-9-yl)ethyl]phosphonic acid (abbreviated as 2PACz) and [2-(3,6-dimethoxy-9H-carbazole-9-yl)ethyl]phosphonic acid (abbreviated as MeO-2PACz).
[0028] In order to better disperse the additives evenly in the carbon slurry while preventing the perovskite material from being corroded by the solvent, the organic solvent used should not corrode the perovskite material, such as butyl acetate.
[0029] The present invention provides a method for preparing a carbon-based perovskite solar cell, the steps of which are as follows: (1) An electron transport layer is prepared on a conductive glass by a chemical bath deposition method. Preferably, the conductive glass is FTO and the electron transport layer is SnO 2 , thickness is 10 nm; (2) FA was deposited by a two-step sequential spin coating method. 0.9 Cs 0.1 PbI 3 The perovskite film is prepared on the electron transport layer in step (1), and annealed on a hot plate at 150° C. for 15 minutes to obtain a perovskite film with a thickness of 800 nm; (3) The conductive carbon paste is coated on the perovskite film in step (2) by scraping, and annealed on a hot plate at 120° C. for 10 minutes to a thickness of 20 μm to obtain a carbon-based perovskite solar cell.
[0030] Example 1 This example is used to prepare conductive carbon paste S1: The organic solvent used in this example is butyl acetate, accounting for 57.1% of the mass percentage of the conductive carbon paste; the binder used is polymethyl methacrylate (PMMA), accounting for 9.0% of the mass percentage of the conductive carbon paste; the conductive carbon materials used are graphite (5000 mesh) and conductive carbon black, the mass ratio of the two is 1:1, accounting for 33.4% of the mass percentage of the conductive carbon paste; the organic additive in this example is 2PACz, accounting for 0.5% of the mass percentage of the conductive carbon paste.
[0031] S2: The liquid and the solid material are mixed, and ball-milled for 12 hours using a planetary ball mill to obtain a conductive carbon slurry that is uniformly mixed, has no obvious visible particles, and has fluidity.
[0032] Example 2 This example is used to prepare conductive carbon paste S1: The organic solvent used in this example is butyl acetate, accounting for 57.1% of the mass percentage of the conductive carbon paste; the binder used is polymethyl methacrylate (PMMA), accounting for 9.0% of the mass percentage of the conductive carbon paste; the conductive carbon materials used are graphite (5000 mesh) and conductive carbon black, the mass ratio of the two is 1:1, accounting for 33.4% of the mass percentage of the conductive carbon paste; the additive used in this example is MeO-2PACz, accounting for 0.5% of the mass percentage of the conductive carbon paste.
[0033] S2: The liquid and the solid material are mixed, and ball-milled for 12 hours using a planetary ball mill to obtain a conductive carbon slurry that is uniformly mixed, has no obvious visible particles, and has fluidity.
[0034] Comparative Example 1 This comparative example is used to prepare conductive carbon paste without additives S1: The organic solvent used in this comparison is butyl acetate, accounting for 57.6% of the mass percentage of the conductive carbon paste; the binder used is polymethyl methacrylate (PMMA), accounting for 9.0% of the mass percentage of the conductive carbon paste; the conductive carbon materials used are graphite (5000 mesh) and conductive carbon black, the mass ratio of the two is 1:1, and the mass percentage of the conductive carbon paste is 33.4%.
[0035] S2: The liquid and the solid material are mixed, and ball-milled for 12 hours using a planetary ball mill to obtain a conductive carbon slurry that is uniformly mixed, has no obvious visible particles, and has fluidity.
[0036] The conductive carbon paste prepared above was used to prepare carbon-based perovskite solar cells. Three examples corresponded to three types of carbon-based perovskite solar cells, corresponding to three different carbon counter electrodes.
[0037] The conductive carbon pastes of Examples 1-2 and Comparative Example 1 of the present invention were prepared into carbon counter electrodes, and then assembled into solar cells. The cell performance was tested and the results were as follows: Figure 1 The JV curve of the solar cell shown in FIG. 1 shows that the carbon counter electrode perovskite solar cell prepared by the conductive carbon paste used in the present invention has a higher open circuit voltage and fill factor, thereby significantly improving the photoelectric conversion efficiency of the cell.
[0038] Table 1 Photovoltaic performance parameters of solar cells prepared in Examples 1-2 and Comparative Example 1 After the conductive carbon pastes of Examples 1-2 and Comparative Example 1 of the present invention were prepared into carbon counter electrodes, scanning electron microscopy (SEM) was used to obtain the following Figure 2 The microstructure of the carbon counter electrode film is shown in Figure 2. Figure 2 It can be concluded that the carbon counter electrode film prepared by the conductive carbon paste adopted in the present invention exhibits a unique microstructure.
[0039] Compared with the comparative example, the optimized carbon counter electrode film presents a uniform, flat and dense surface structure, which can effectively improve the physical or chemical defects formed at the contact interface between the perovskite and the carbon counter electrode, reduce the charge transfer loss, and better form the energy level matching between the two. The introduction of self-assembling organic small molecules can provide more hole transmission channels, effectively reduce the charge recombination loss, and improve the energy level mismatch problem between the carbon electrode and the perovskite layer in the hole-free perovskite solar cell, thereby greatly improving the photoelectric conversion efficiency of the device.
[0040] The above embodiments are preferred implementation modes of the present invention, but the implementation modes of the present invention are not limited to the above embodiments. Any other changes, modifications, substitutions, combinations, and simplifications that do not deviate from the spirit and principles of the present invention should be equivalent replacement methods and are included in the protection scope of the present invention.
Claims
1. A conductive carbon paste that can be used for perovskite solar cells, characterized in that including conductive carbon material, solvent, binder, and additive; The structural composition of the additive molecule includes an anchoring group, a spacer group and a functional group; the functional group includes at least one of carbazole, triphenylamine, thiophene, phenothiazine, triazaanthracene and graphene; the spacer group includes at least one of an aliphatic chain and an aromatic ring; the anchoring group includes at least one of phosphonic acid, carboxylic acid, cyanoacetic acid, cyanophosphoric acid, sulfonic acid and silane.
2. The conductive carbon paste for perovskite solar cells according to claim 1, characterized in that: The additive is at least one of [2-(9H-carbazole-9-yl)ethyl]phosphonic acid and [2-(3,6-dimethoxy-9H-carbazole-9-yl)ethyl]phosphonic acid.
3. The conductive carbon paste for perovskite solar cells according to claim 1, characterized in that: The conductive carbon material is a conductive carbon material, including at least one of carbon black, graphite, graphene, and carbon nanotubes; The solvent is at least one of isopropyl titanate, tetrabutyl titanate, butyl acetate, ethanol, terpineol, ethyl acetate, glacial acetic acid, and γ-butyrolactone; The binder is at least one of ionic liquid, ethyl cellulose, polyvinyl acetate, hydroxypropyl cellulose, polyvinyl pyrrolidone and polymethyl methacrylate; wherein the ionic liquid includes at least one of 1-octyl-3-methylimidazolium hexafluorophosphate and 1-butyl-3-methylimidazolium hexafluorophosphate.
4. The conductive carbon paste for perovskite solar cells according to claim 1, characterized in that: In the conductive carbon paste that can be used for perovskite solar cells, the amounts of conductive carbon material, solvent, binder, and additives meet the following requirements: the mass of the conductive carbon material accounts for 25-40% of the mass of the conductive carbon paste, the mass of the solvent accounts for 50-65% of the mass of the conductive carbon paste; the mass of the binder accounts for 6-12% of the mass of the conductive carbon paste; and the mass of the additive accounts for 0.1-2.0% of the mass of the conductive carbon paste.
5. A method for preparing a conductive carbon paste for perovskite solar cells according to any one of claims 1 to 4, characterized in that The following steps are involved: After the raw materials are mixed together, they are ground or stirred to make the resulting slurry uniformly mixed, free of obvious visible particles, and fluid, thereby obtaining a conductive carbon slurry that can be used for perovskite solar cells.
6. Use of the conductive carbon paste for perovskite solar cells according to any one of claims 1 to 4 in perovskite solar cells.
7. A carbon counter electrode for a perovskite solar cell, characterized in that The conductive carbon paste for perovskite solar cells according to any one of claims 1 to 4 is prepared by blade coating or screen printing.
8. A perovskite solar cell, characterized in that It comprises the carbon counter electrode, the perovskite layer and the electron transport layer as claimed in claim 7.
9. The perovskite solar cell according to claim 8, characterized in that: The perovskite solar cell, wherein the perovskite is an ABX3 structure, wherein A is at least one of methylamine, formamidine, cesium and rubidium, B is at least one of lead, tin, silver, antimony, copper and bismuth, and X is at least one of chlorine, bromine, iodine, thiocyanate and acetate; The electron transport layer includes at least one of SnO2, TiO2, ZnO, PCBM, and C60.
10. The perovskite solar cell according to claim 8, characterized in that: The perovskite solar cell also has a hole transport layer, which includes a hole transport layer prepared from at least one of small molecules, polymers, and inorganic hole transport materials.